Islamic Law Review Of Cadre Wage Cuts (Case Study Of Posyandu Anggrek, Kelayan Luar District) - Anita, Noor (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract Humans work to find additional income for their daily lives. The desire of the cadres, the majority of whom are housewives, to work in the hope of wages is exploited by many good people, as happened at Posyandu Anggrek, Kelayan Luar Subdistrict. Where there is a cut in cadre wages which is very detrimental to the cadres. Therefore, researchers are interested in researching cadre wage cuts and the factors causing cadre wage cuts at Posyandu Anggrek, Kelayan Luar Subdistrict. The method used in this research is empirical legal research. The results of this research indicate that the wage cuts for cadres at Posyandu Anggrek, Kelayan Subdistrict have not clearly regulated wages. There are still those who do not fulfill their obligations so that workers' rights are not fulfilled, where the rights that three out of four cadres do not get regarding wages at Posyandu Anggrek, Kelayan Luar Subdistrict, namely cadres do not receive information regarding the value and amount of wages they will receive and giving wages that are not commensurate with the results of the work that has been done. The cause of the wage cuts that occurred at Posyandu Anggrek, Kelayan Luar Subdistrict, was due to the addition of PMT (Supplemental Food Provision) money which should not have been the responsibility of the cadres. Keywords: Islamic Law, Wage Deductions, Cadre. Abstrak Manusia bekerja untuk mencari penghasilan tambahan untuk kehidupan sehari-hari. Keinginan para kader yang mayoritas adalah ibu rumah tangga untuk bekerja dengan harapan mendapatkan upah dimanfaatkan oleh banyak orang baik, seperti yang terjadi di Posyandu Anggrek Kecamatan Kelayan Luar. Dimana terjadi pemotongan upah kader yang sangat merugikan para kader. Oleh karena itu, peneliti tertarik untuk meneliti pemotongan upah kader dan faktor-faktor penyebab pemotongan upah kader di Posyandu Anggrek Kecamatan Kelayan Luar. Metode yang digunakan dalam penelitian ini adalah penelitian hukum empiris. Hasil penelitian ini menunjukkan bahwa pemotongan upah kader di Posyandu Anggrek Kecamatan Kelayan belum mengatur secara jelas mengenai upah. Masih ada yang tidak memenuhi kewajibannya sehingga hak-hak pekerja tidak terpenuhi, dimana hak-hak yang tidak didapatkan oleh tiga dari empat kader terkait pengupahan di Posyandu Anggrek Kelurahan Kelayan Luar yaitu kader tidak mendapatkan informasi terkait nilai dan jumlah upah yang akan diterimanya serta pemberian upah yang tidak sepadan dengan hasil pekerjaan yang telah dilakukan. Penyebab pemotongan upah yang terjadi di Posyandu Anggrek Kecamatan Kelayan Luar dikarenakan adanya penambahan uang PMT (Pemberian Makanan Tambahan) yang seharusnya tidak menjadi tanggung jawab kader. Kata Kunci: Hukum Islam, Pemotongan Upah, Kader.